Impressões e ações de professores que visitaram o centro regional de ciências nucleares do Centro-Oeste: duas décadas do acidente com o Césio-137 em Goiânia - GRASSI, Giovanni (2010)
The objective of this study was to analyze contextually how impressions of visitors to the Information Center of the Regional Center of Nuclear Sciences of the Midwest (CI-CRCN-CO) in the anniversary month of twenty years of the accident with the Cesium-137 in Goiânia, September 2007, in others words, qualitatively analyze the actions of popular science pursued for this space non-formal education. Using some of the theoretical references, we discuss the formal and non-formal, communication and popularization of science and functions of museums and science centers to analyze the activities of an institution which, besides carrying out research and make the monitoring of environment near the deposits where the garbage generated by the accident with cesium-137, is visited in order to inform the population about the episode occurred in September 1987. The data collected through documentary analysis and semi-structured interviews allowed a qualitative analysis taking into account the cultural, political, social and academic actions performed by the Information Center CRCN-CO. Respondents consider that the aforementioned institution is helping to expand scientific knowledge of the population, raising the critical sense of scientific production and generating developments of its activities in schools that visit.